2023
DOI: 10.3389/fphys.2023.1075641
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota dependant trimethylamine N-oxide and hypertension

Abstract: The human gut microbiota environment is constantly changing and some specific changes influence the host’s metabolic, immune, and neuroendocrine functions. Emerging evidence of the gut microbiota’s role in the development of cardiovascular disease (CVD) including hypertension is remarkable. There is evidence showing that alterations in the gut microbiota and especially the gut-dependant metabolite trimethylamine N-oxide is associated with hypertension. However, there is a scarcity of literature addressing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 169 publications
(290 reference statements)
0
10
0
Order By: Relevance
“…SCFAs could affect BP by activating the G protein‐coupled receptor pathway when they were absorbed by the intestinal epithelium into the host circulatory system 52 . TMAO could induce oxidative stress and inflammatory reaction in vascular endothelium, damage the production and bioavailability of endothelial nitric oxide, resulting in endothelial dysfunction, vasoconstriction and elevated BP 53 . In addition, the GM may also stimulate sympathetic drives through enteric nervous system‐brain interactions or by promoting neuroinflammation, while increased sympathetic activity may promote the development of hypertension by stimulating low‐grade systemic inflammation 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs could affect BP by activating the G protein‐coupled receptor pathway when they were absorbed by the intestinal epithelium into the host circulatory system 52 . TMAO could induce oxidative stress and inflammatory reaction in vascular endothelium, damage the production and bioavailability of endothelial nitric oxide, resulting in endothelial dysfunction, vasoconstriction and elevated BP 53 . In addition, the GM may also stimulate sympathetic drives through enteric nervous system‐brain interactions or by promoting neuroinflammation, while increased sympathetic activity may promote the development of hypertension by stimulating low‐grade systemic inflammation 54 .…”
Section: Discussionmentioning
confidence: 99%
“… 52 TMAO could induce oxidative stress and inflammatory reaction in vascular endothelium, damage the production and bioavailability of endothelial nitric oxide, resulting in endothelial dysfunction, vasoconstriction and elevated BP. 53 In addition, the GM may also stimulate sympathetic drives through enteric nervous system‐brain interactions or by promoting neuroinflammation, while increased sympathetic activity may promote the development of hypertension by stimulating low‐grade systemic inflammation. 54 We conducted subgroup analysis based on sample size, study population, and sequencing methods, and found that the study population may be the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Diets higher in animal foods tend to be associated with a greater risk of HTN [ 38 , 39 , 86 – 88 ]. They contain higher levels of saturated fat [ 89 , 90 ] and advanced glycation end products (AGEs) [ 91 ] and promote the formation of trimethylamine-N-oxide (TMAO) [ 92 ], which have all been linked to HTN and CVD. A more comprehensive review of the health harms of animal food consumption can be found elsewhere [ 93 •].…”
Section: Mechanistic Evidencementioning
confidence: 99%
“… 7 TMAO promotes the proliferation and migration of pulmonary artery smooth muscle cells, by upregulating inflammatory factors 11,68 . Endothelial dysfunction has also been shown to be influenced by TMAO via inflammatory pathways that lead to endothelial hyperpermeability 58,69 . Furthermore, TMAO promotes the production of reactive oxygen species that adds to the impairment of endothelial function 58,70 .…”
Section: The Role Of Gut Microbiota In Pulmonary Hypertension (Ph)mentioning
confidence: 99%